Золоті прикраси у вигляді голови Гери - Русяєва, М.В. (Археологія, 1994)
У публікації дається аналіз чотирьох золотих прикрас у вигляді жіночої голови, визначається їх іконографія, хронологія і місце виготовлення. В разных местах Северного Причерноморья (Ольвия, Пантикапей, скифский курган у села Великая Бслозерка) бьши найдены украшения в виде женской головы; происхождение четвертой подвески, хранящейся в Британском музее, не установлено. Предлолагается, что это изображения головы Геры, в разных вариантах скопированные со знаменитой статуи Поликлета. На основании стилистических особенностей данные изделия можно датировать первой половиной IV в. до н. э. и считать их работой афинских торевтов. Adornments looking like woman’s head were found in different points of the North Black Sea territory (Olbia, Panticapci, Scythian burial mound’ near vil. Velikaya Belozerka); the origin of the fourth pendant kept at the British museum is not determined. It is supposed that these adornment depicts Hera’s head which was copied in different variants from the famous statue made by Polycletus. Stilistic peculiarities permit dating these articles the first half of the 4th cent. B.C. and treating them as work of Athens thorevts.